Mid-term results of water vapor thermal therapy in patients with lower urinary tract symptoms related to benign prostatic hyperplasia - Ghahhari, Jamil; Sountoulides, Petros; Campobasso, Davide; Faieta, Alessio; Sessa, Francesco; Viola, Lorenzo; Siena, Giampaolo; Cianci, Filippo; Cindolo, Luca (Frontiers in Urology, 2022)
Objective In this study, we evaluate the short- and mid-term results of water vapor thermal therapy (WVTT) for LUTS (lower urinary tract symptoms) due to benign prostatic hyperplasia (BPH). Methods Patients with LUTS due to BPH who underwent WVTT from September 2019 to April 2022 were included in this prospective, single-center study. Data regarding functional and sexual outcomes were evaluated by validated questionnaires as well as uroflowmetry, urinalysis and cultures, digital rectal examination, serum prostate-specific antigen, and transrectal ultrasound. The patients were followed-up with 3, 6, 12, and 18 months after the procedure. Results Eighty-four men were treated. Mean ± SD prostate volume, operative time, and hospital stay were 76.9 ± 26.3 ml, 14 ± 18.5 min, and 0.9 ± 0.7 days, respectively. The catheter was removed after 7 ± 4.4 days. A significant (p < 0.05) improvement in Qmax, IPSS, QoL, OAB-q SF, ICIQ-SF, and IIEF- 5 from the baseline at the last follow-up (18 months) was recorded. Seventy-six (90%) patients reported a significant improvement in ejaculatory function (de novo dry ejaculation in 4 patients). Early (≤30 days) postoperative complications were reported in 70% of patients, all grade 1 according to Clavien–Dindo. No late (>30 days) Clavien–Dindo >1 procedure-related complications occurred. Three patients required reoperation (6–12 months after surgery). Conclusion WVTT is an effective and safe treatment for the management of LUTS due to BPH in the short- and mid-term follow-up, and it provides negligible sequelae with respect to ejaculation.